2020
DOI: 10.7554/elife.56029
|View full text |Cite
|
Sign up to set email alerts
|

Recent shifts in the genomic ancestry of Mexican Americans may alter the genetic architecture of biomedical traits

Abstract: People in the Americas represent a diverse continuum of populations with varying degrees of admixture among African, European, and Amerindigenous ancestries. In the United States, populations with non-European ancestry remain understudied, and thus little is known about the genetic architecture of phenotypic variation in these populations. Using genotype data from the Hispanic Community Health Study/Study of Latinos, we find that Amerindigenous ancestry increased by an average of ~20% spanning 1940s-1990s in M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 54 publications
4
22
0
Order By: Relevance
“…Similarly, sociocultural practices that govern mate choice or sex-specific contributions from the source populations will leave signatures in patterns of genetic ancestry. Individual behaviours such as mating preferences or long-range migration can exhibit ancestry biases in which the ancestry patterns in the subset of the population that migrates are not representative of the whole admixed population, potentially driven by correlations between ancestry and visible traits like skin pigmentation or socioeconomic differences [64][65][66][67][68][69]. Simple models of admixture often assume that individuals mate randomly; however, admixed human populations show evidence of positive assortative mating, with mating pairs often correlated in global ancestry proportion [67,[70][71][72].…”
Section: Inferring Population Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, sociocultural practices that govern mate choice or sex-specific contributions from the source populations will leave signatures in patterns of genetic ancestry. Individual behaviours such as mating preferences or long-range migration can exhibit ancestry biases in which the ancestry patterns in the subset of the population that migrates are not representative of the whole admixed population, potentially driven by correlations between ancestry and visible traits like skin pigmentation or socioeconomic differences [64][65][66][67][68][69]. Simple models of admixture often assume that individuals mate randomly; however, admixed human populations show evidence of positive assortative mating, with mating pairs often correlated in global ancestry proportion [67,[70][71][72].…”
Section: Inferring Population Historymentioning
confidence: 99%
“…Similarly, temporal changes in ancestry proportion within a population may be caused by time-varying social dynamics. Spear et al [69] found a significant increase in Amerindigenous ancestry in Mexican American populations over time, potentially owing to differences in ancestry in the migrating population over time and fecundity correlated with ancestry.…”
Section: Inferring Population Historymentioning
confidence: 99%
“…PhenoGram plots [140] were constructed for genetic variants associated with (A) ALL susceptibility, and/or (B) ALL patient outcomes (i.e., relapse and response to therapy). Genetic variants included in the PhenoGrams were identified in the NHGRI-EBI catalog of human genome-wide association studies (GWAS Catalog) [141] and included in published GWAS for acute lymphoblastic leukemia (ALL) [15,16,[18][19][20][24][25][26][27]32,135,136] or for outcomes of ALL [142][143][144][145][146][147][148][149][150] . We also included some variants described in additional papers included in this review for ALL susceptibility [17,[21][22][23][28][29][30][31] and ALL patient outcomes [21,139] .…”
Section: Genetic Variants Contribute To Racial/ethnic Disparities In All Incidencementioning
confidence: 99%
“…Finally, to ascertain that our patients share the Mexican population (MXL) genetic background, as reported in the 1KGP, a global ancestry analysis was performed. In this context and considering that Mexicans present a remarkable genetic diversity due to population admixture, we decided to contrast all SNVs data of these 3 Mixe patients against other populations beside the MXL, including Native-Americans (NAT), Utah residents with Northern and Western European ancestry (CEU), and Yoruba in Ibadan, Nigeria (YRI); similar to how the Mexican population structure has been analyzed in previous studies [25,26]. Using this appoach, it was observed that the MXL population presents an ancestry pattern with native and european components predominance (NAT:46.59% and CEU:48.44%, respectively).…”
Section: Mixe Populationmentioning
confidence: 99%